(untitled) (Tanzania Medical Journal, 2016)
Background: Surgical removal of the eye is the last alternative to manage several eye conditions. Removal of the eye evokes emotional, mental, behavioral, psychological and economical challenges to the affected individual and the family as well. Understanding of the proper indications for surgical eye removal is of paramount importance for establishing prevention strategies.Objective: To determine the indications for surgical eye removal at two tertiary eye hospitals in Dar Es Salaam.Methodology: This was a retrospective descriptive study conducted at two tertiary eye clinics of Muhimbili and Comprehensive Community Based Rehabilitation Hospitals in Dar es Salaam. The study involved review of 248 case notes of patients who had undergone surgery for removal of the eye for a period of 20 months from January 2011 to August 2012. Demographic characteristics, diagnosis and surgical procedure were recorded on a structured questionnaire. Data was analyzed using SPSS version 17 software. Frequency tables were used to summarize data. Chi square test were used to test for statistical significance of an association between variables.Results: A total of 306 patients had undergone surgical eye removal from January 2011 to August 2012. Two hundred forty eight case notes with complete information (response rate of 245/306 (81%) were included in the analysis. About 61% of case notes included in the analysis were of male patients.The commonest indications for Surgical eye removal were infections (endophthalmitis/panophthalmitis) (35.8%), tumours (24.2%) and trauma (21.4%). Evisceration was the commonest procedure, it was performed to 178(71.8%) patients; it was followed by enucleation (19.4%) and exenteration (8.9%). Two hundred thirty three (94.0%) eyes were blind and 6(2.4%) had visual impairment pre-operatively. Conclusion: The commonest indications of surgical eye removal at MNH and CCBRT in Dar es Salaam were infections (endophthalmitis/panophthalmitis), tumours and trauma. Earlier diagnosis and management of eye infections and tumours can help in improving post-treatment visual outcome and reduce instances of surgical eye removal. Creation of awareness among the general public and primary health care providers about improving health seeking behavior and timely referral of patients with eye conditions is recommended.